Biomass and nutrient flow dynamics and sustainability practices to de-risk environmental challenges in the Sub-Saharan Africa farming system - Guindo, M.; Traore, B.; Zemadim, Birhanu (Elsevier, 2024)
In sub-Saharan Africa, productivity risks stem from weather variability, while environmental risks include soil nutrient depletion due to unsustainable farming practices that include monoculture, inadequate or lack of soil and water conservation measures, and low-nutrient application. As a result, shifts from the prevailing fallow system to permanent cultivation lead to soil degradation. The present study aimed to quantify the fluxes of biomass, nutrients, and nutrient balances from different fertilizer sources to de-risk the challenges related to agriculture and the environment in Mali. A farm household survey was conducted over two years (July 2018 to June 2020) with 45 households. The survey enabled us to categorize farm households into three typologies: high resource endowment (HRE), medium resource endowment (MRE), and low resource endowment (LRE). Data on sustainability indicators from cropland, livestock, farm input use, and redistribution units enabled the analysis of biomass and nutrient flow dynamics from households to farmlands and vice versa. The nutrient monitoring (NUTMON) tool generated nutrient flows and balances. Results showed that the total annual biomass collected per hectare by HRE (22.3t) is significantly higher than that collected by MRE (13.4t) and LRE (5.35t) farms (P < 0.001). Compared to LRE (10.3 t ha 1 year 1 ), HRE and MRE farmers produced six times (60 t ha 1 year 1 ) and three times (34 t ha 1 year 1 ) more manure, respectively. Farm households with better endowment status observed a higher rate of nutrient utilization. For the major crops, nutrient application rates of HRE farms in kg ha 1 (cotton: 12.6 N, 4.2 P, 18.2 K) and (maize: 9.18 N, 2.34 P, 10.7 K) were significantly higher than that of MRE and LRE farms (P < 0.01). The study confirms that household endowment status determines farmlands' nutrient flows and fertility levels. Quantifying biomass transport and understanding nutrient flow dynamics enable the derivation of context-specific solutions to reduce risks associated with productivity and the environment.